Release of inorganic phosphate during activity in mammalian non-myelinated nerve fibres - Maire, J. C. (1980)
1. The efflux of labelled phosphate was measured in desheathed rabbit vagus nerve at rest and during activity. 2. In solutions with 2 mM-phosphate and 1 mM-K the rate constant of the resting efflux was 2·7 × 10(-3) min(-1); stimulation caused an extra fractional loss of 2·8 × 10(-6) impulse(-1). 3. Lowering the phosphate concentration decreased the resting and the stimulated efflux; with 0·2 mM-phosphate the corresponding values were 1·9 × 10(-3) min(-1) and 1·8 × 10(-6) impulse(-1), respectively. 4. Increasing the K to 5·6 mM decreased both resting and stimulated efflux. 5. Lowering the temperature decreased the resting efflux with a Q(10) of 2·9 and the stimulated efflux with a Q(10) of 8·1. 6. Chromatography of the effluent showed that at rest and during activity at least 96% of the radiophosphate was in the orthophosphate fraction. 7. Replacing the Na of the solution by Li lowered the rate constant of the resting efflux to 0·8 × 10(-3) min(-1) and abolished the extra release during activity, without reduction of the action potential. 8. The presence of ouabain did not affect the resting efflux, except at 100 μM, when a transient reduction was found. The extra fractional loss was not affected with 0·001 μM; with 0·01-0·5 μM, it was reduced without much change in the action potential, and abolished at higher concentrations. 9. The results agree with the hypothesis that the extra release results from an increase in internal inorganic phosphate caused by increased break-down of ATP during recovery. 10. Comparison with the O(2) consumption shows that about 1% of the inorganic phosphate liberated at the inside of the axons escapes to the outside.